Web mobile integration in teaching heritage module at Port Dickson Polytechnic - Isham Shah Hassan; Zaharuddin Saaya; Nur Athirah Ibrahim (Proceedings of AICS - Social Sciences, 2013)
Computers and Internet have successfully provided students with various online educational services. With the latest developments in the mobile technology, new methods are emerging to provide educational services through mobile technologies such as mobile phones and PDAs. By providing the educational services using the wireless medium, the educational institutions can facilitate self-access learning.  By using the mobile educational services, lecturers and students can access the services anytime and anywhere they want. This paper discusses the possibility of providing architectural heritage studies on web application through mobile technology. This offers a new approach in architectural education, namely imparting knowledge, or facilitating the imparting of knowledge, through a medium other than the traditional methods used in polytechnic. It does not seek to replace the conventional methods of teaching, which have traditionally been through lecture classes and design studios. It merely aspires to bridge some of the gap that is found between the two and thereby promote better understanding of architectural knowledge. The case study is an important tool in architectural education. Students learn by analyzing, comparing and evaluating aspects of important architectural works. By providing a tool by which this evaluation is facilitated and enhanced through the process of associative thinking, architectural learning is enriched. The paper will conduct formative evaluation of the student projects with the aim to test the feasibility of providing mobile educational services for diploma level architectural students in Port Dickson Polytechnic.  The study found that the mobile learning can be a useful complement to the current computer based learning.Keywords: Heritage, Web, Mobile Technology, Mobile Learning